Analysis of boundary layer MHD Darcy-Forchheimer radiative nanofluid flow with soret and dufour effects by means of marangoni convection. (February 2021) - Jawad, Muhammad; Saeed, Anwar; Kumam, Poom; Shah, Zahir; Khan, Aurangzeb
Abstract: In the current article, the analysis of magnetohydrodynamic laminar flow past a vertical permeable surface is presented. The flow is considered in the existence of Dufour as well as Soret effects. There is a diffusion-thermo process when heat transmission is encouraged by the concentration gradient and thermo diffusion process when the transfer of mass is encouraged by the thermal gradient. The set of partial differential equations (PDEs) for a modeled problem is changed into a set of ordinary differential equations by applying selected non-dimensional similarity transformations. The semi-analytical method HAM is used to determine a solution for the modeled problem. The features of flow characteristics such as velocity, temperature, and concentration profiles in response to the variations of the emerging parameters are simulated and examined in detail. This research article aims to analyze the impacts of surface tension thermo-solutal quotient, Soret parameter, Dufour parameter, Schmidt number, and Prandtl number on the fluid momentum, transfer of heat, and mass. It is noticed in this article that, the gradient of temperature and concentration at the surface is escalated with enhancement in thermo-solutal surface tension. It is further noted that augmentation in the Prandtl number augmented the transfer in heat.